Prognostic significance of 18F-FDG PET/CT indices in metastatic renal cell cancer and evaluation of revised IMDC risk model by including 18F-FDG PET-CT parameters. (May 2023) - Arikan, Rukiye; Ozguven, Salih; Telli, Tugba Akin; Isik, Selver; Demircan, Nazım Can; Basoglu, Tugba; Yasar, Alper; Celebi, Abdussamet; Filizoglu, Nuh; Ustun, Hilal Sagiroglu; Tinay, Ilker; Ones, Tunc; et al.
Background: Prognostic markers in metastatic renal cell cancer (mRCC) are still insufficient. Any prognostic model objectively determines disease burden. Purpose: To investigate the relationship between 18-fluorodeoxyglucose (18F-FDG) positron emission tomography/computed tomography (PET/CT) parameters and outcomes in mRCC, and to define a revised International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) model for the intermediate-risk group. Material and Methods: A retrospective study of mRCC was conducted. To investigate the prognostic significance of 18F-FDG PET/CT parameters, maximum standardized uptake value (SUVmax ), total lesion glycolysis (TLG), and metabolic tumor volume (MTV) were determined in pre-treatment images. Cutoff values were defined by ROC curve analyses and their association with outcomes was analyzed. Additionally, a TLG-adjusted IMDC model was created by stratifying intermediate-risk group patients according to TLG levels. Results: The study included 52 patients. The disease control rate (DCR) was 61.5% and median overall survival (OS) was 18 months (95% confidence interval=9.2–25.8). In the univariate analyses, IMDC score, MTV, and TLG were prognostic factors for Disease Control Rate (DCR), and Eastern Cooperative Oncology Group (ECOG)-Performance Status (PS), IMDC score, lactate dehydrogenase (LDH), treatment option, MTV, and TLG were prognostic factors for OS ( P  < 0.05 each). In the multivariate analyses, MTV was an independent prognostic factor for DCR, and ECOG-PS, LDH, IMDC score, and TLG were independent prognostic factors for OS. According to the revised-IMDC model, the intermediate-favorable group showed longer OS than the intermediate-unfavorable group. Conclusion: Pretreatment MTV was independent prognostic factor for DCR and ECOG-PS, LDH, IMDC score, and TLG were independent prognostic factors for OS. Revised-IMDC model could identify patients with a worse prognosis among the IMDC intermediate-risk group.